Large‐Scale Geographical Variations and Climatic Controls on Crown Architecture Traits. Issue 2 (20th February 2020) - Su, Yanjun; Hu, Tianyu; Wang, Yongcai; Li, Yumei; Dai, Jingyu; Liu, Hongyan; Jin, Shichao; Ma, Qin; Wu, Jin; Liu, Lingli; Fang, Jingyun; Guo, Qinghua
Abstract: Crown architecture is a critical component for a tree to interact with the ambient environment and to compete with neighbors. However, little is known regarding how climate variability may shape crown architecture traits across large geographical extents and whether crown architecture traits have coordinated variations with trunk and leaf traits to climate gradients. Here we used Quercus mongolica trees as an example, used the cutting‐edge terrestrial laser scanning technique to accurately characterize their crown architecture traits, and explored their variabilities along with environmental variability across large climate gradients in northern China. Our results showed that there are significant spatial variations in trunk, crown, and leaf traits even for the same genetic group across large environmental gradients. Tree height and leaf size had tight covariations with precipitation (| R |> 0.8, p < 0.01). We also observed coordinated variations among crown architecture traits related to canopy shape (e.g., primary branch insertion angle, chord length ratio), trunk traits (e.g., tree height), leaf traits (e.g., specific leaf area), and climate variability, highlighting there are likely fundamental evolutionary strategies regulating these covariations. With a projected drier and hotter climate scenario in this region, our results further suggest trees are expected to transit from a "tree shape" to a "shrub shape, " with large ecological and ecophysiological impacts on this region. Plain Language Summary: Trees under different environmental conditions can show vast diversity in crown architectures. Understanding patterns and proximate causes of such diversity is a central question in plant ecology, with important implications for predicting future vegetation dynamics with climate change. Here, we combined the cutting‐edge terrestrial laser scanning technology and field measurements to investigate the role of crown architecture in the evolutionary strategy development of Quercus mongolica trees in northern China with large climate gradients. Our findings provide new insights on the hypothesis of how crown architecture traits coordinated with trunk and leaf traits to balance the light and water demands of a tree and highlight the significance of long‐neglected crown architecture in tree evolutionary strategy, with important implications in future vegetation dynamic prediction studies. Key Points: Significant spatial variations in crown architecture traits are observed across large climate gradients Trunk and leaf traits are correlated with precipitation, while crown architecture is correlated with both temperature and precipitation Crown shape related architecture traits coordinate with trunk and leaf traits tightly to adapt to changes in environmental conditions